The internal drainage as a differentiation factor in Oxisols of Distrito Federal, Brazil - Campos, Patrícia Maurício; Lacerda, Marilusa Pinto Coelho; Silva, Cícero Lopes da; Sá, Marcos Aurélio Carolino de; Sousa, Djalma Martinhão Gomes de (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to determine the influence of soil physicohydric characteristics on Oxisols diagnostic attributes. Morphological, chemical, physical, mineralogical and physicohydric attributes were surveyed in profiles of five Latossolos Vermelhos (Rhodic Haplustox, LV) and of five Latosssolos Vermelho-Amarelos (Typic Haplustox, LVA), considered representative of this kind of Oxisols in Distrito Federal, Brazil. Besides the soil diagnostic attributes characterization, the water-table oscillation was monitored using 2.5-m depth observation wells, during one year. The studied Oxisols were considered chemically and physically similar. However, they differed as to morphological and mineralogical characterization, with the presence of concretionary horizons and goethite in the LVA. Goethite stability in this soils was influenced by the water-table oscillation. The presence of concretionry horizons in LVA caused an internal drainage deficiency, which resulted in lower saturated hydraulic conductivity and lower variation of the water-table levels. Therefore, LVA soils show lower agricultural potential than LV ones, in Distrito Federal. Oxisols physicohydric characteristics have little influence on soil diagnostic attributes, except for iron oxides mineralogy, which show increased contents of goethite in low internal drainage conditions.